1990
DOI: 10.1080/02699939008408081
|View full text |Cite
|
Sign up to set email alerts
|

The effect of power on susceptibility to emotional contagion

Abstract: This study explored two questions : Do people tend to display and experience other people's emotions? If so, what impact does power have on people's susceptibility to emotional contagion? We speculated that the powerless should pay more attention to their superiors (than their superiors pay to them) and should thus be especially likely to "catch" their superiors' emotions as well . College students, given the role of "teacher" (powerful person) or "learner" (powerless person), observed videotapes of another (f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
138
0
3

Year Published

1992
1992
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 233 publications
(145 citation statements)
references
References 12 publications
4
138
0
3
Order By: Relevance
“…Interestingly, though, in a lab experiment examining emotional contagion and dyadic power relations, Hsee et al (1990) found that the power holder was more prone to receive contagion from the subordinates than the reverse. Perhaps this is one of the ways that leaders are empowered by their followers (e.g., Barnard, 1938).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, though, in a lab experiment examining emotional contagion and dyadic power relations, Hsee et al (1990) found that the power holder was more prone to receive contagion from the subordinates than the reverse. Perhaps this is one of the ways that leaders are empowered by their followers (e.g., Barnard, 1938).…”
Section: Discussionmentioning
confidence: 99%
“…Contagion of emotions has been examined as far back as 400 B.C., when Hippocrates coined the term "hysteria" to refer to the passing of an agitated state from unmarried women to other unmarried women (Veith, 1965). Current psychological contagion research examines less dramatic yet more prevalent day-to-day contagion effects (e.g., Hsee et al, 1990;Sullins, 1991;Hatfield, Cacioppo andRapson, 1992, 1994) Emotional contagion has long been viewed as a type of social influence (Schacter, 1959: 15;Levy & Nail, 1993) that can occur at both the conscious and unconscious levels (Kelly & Barsade, 2001;Druckman & Bjork, 1994;Totterdell, 2000).…”
Section: Emotional Contagionmentioning
confidence: 99%
“…This kind of mimicry occurs when one person unintentionally and effortlessly copies another person's posture or body movements without either one being aware (Chartrand & Lakin, 2013;Chartrand & van Baaren, 2009). Mimicry may extend to the contagion of facial expressions (Bavelas, Black, Lemery, & Mullett, 1986, 1987 Dimberg, Thunberg, & Elmehed, 2000;Hsee, Hatfield, Carlson, & Chemtob, 1990), moods (Hsee et al, 1990;Neumann & Strack, 2000) and speech (Giles & Powesland, 1975;Neumann & Strack, 2000).…”
Section: Abstract: Mimicry Imitation Nonverbal Behaviour Neurocognmentioning
confidence: 99%
“…In particular, a large body of research shows that people a diverse range of behaviours like facial expressions (Bavelas, Black, Lemery, & Mullett, 1986, 1987Dimberg, Thunberg, & Elmehed, 2000;Hsee, Hatfield, Carlson, & Chemtob, 1990), sniffing (Arzi, Shedlesky, Secundo, & Sobel, 2014) and speech (Giles & Powesland, 1975;Neumann & Strack, 2000), as well as overt choices (Harakeh, Engels, Van Baaren, & Scholte, 2007;Hermans et al, 2012;Quigley & Collins, 1999;Tanner et al, 2008;Webb, Eves, & Smith, 2011). It is not clear whether all of these different forms of mimicry reflect similar mechanisms or how they relate to one another.…”
Section: What Is the Relationship Between Different Kinds Of Mimicry?mentioning
confidence: 99%
“…Interpersonal symmetry has been reported in many contexts and across sensory modalities: for instance, patterns of speech (Cappella & Panalp 1981, Neumann & Strack 2000, facial expression (Hsee et al 1990) and laughter (Young & Frye 1966). Increased symmetry is associated with increased rapport and affinity between conversants (LaFrance 1982;Bernieri 1988).…”
Section: Introductionmentioning
confidence: 99%